2017
DOI: 10.1080/00423114.2017.1313435
|View full text |Cite
|
Sign up to set email alerts
|

Switch Panel wear loading – a parametric study regarding governing train operational factors

Abstract: The acting forces and resulting material degradation at the running surfaces of wheels and rail are determined by vehicle, track, interface and operational characteristics. To effectively manage the experienced wear, plastic deformation and crack development at wheels and rail, the interaction between vehicle and track demands a system approach both in maintenance and in design. This requires insight into the impact of train operational parameters on rail-and wheel degradation, in particular at switches and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The study of wear in wheel-track systems is the subject of many works [1][2][3][4][5][6][7][8][9][10][11]. In these works, the task of wear is addressed by presenting different models of wheel-rail interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of wear in wheel-track systems is the subject of many works [1][2][3][4][5][6][7][8][9][10][11]. In these works, the task of wear is addressed by presenting different models of wheel-rail interaction.…”
Section: Introductionmentioning
confidence: 99%
“…They connect neighbouring tracks and enable railway vehicles to change direction of travel. The basic type is the ordinary turnout consisting of switch blades (2), closure rails (2, 3), a crossing frog (4), turnout sleepers, and setting devices. The crucial element of each turnout is the Energies 2021, 14, 7520 2 of 39 frog (4) that enables the wheels of railway vehicles to roll over the place of rail crossing.…”
Section: Introductionmentioning
confidence: 99%
“…The wear observed by Bayer can be divided into different categories, abrasion (causing high friction levels between the surfaces), impact (causing plastic deformation, and cracks), and delamination (causing material removal from the surface). The side abrasion wear in the switch panels has been the subject of research studies, to understand the loading and degradation of S&C [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical and experimental studies appeared in the last years dealing with the dynamic interaction and deterioration mechanisms in switches and common crossings. A parametric study was carried out in [7] by means of vehicle-track simulations and it presented the impact of the train operational parameters on rail and wheel degradation. It was found that switch rail lateral loading at 1:9 type turnout is significantly influenced by the level of wheel-rail friction and less by the travel direction.…”
Section: Introductionmentioning
confidence: 99%